2014
DOI: 10.4995/eurocall.2014.3639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iPod Touch-Supported Repeated Reading on the English Oral Reading Fluency of L2 students with Specific Learning Difficulties

Abstract: <span>In recent years the use of new technologies has been extensively explored in different aspects of language learning pedagogy. The objective of this research was to investigate the impact Repeated Reading activity, supported by iPod Touch could have on the English Oral Reading Fluency (ORF) of second language university students with Special Learning Difficulties (SpLD) at Cyprus University of Technology. As part of their university courses, students have two compulsory English courses. Due to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“…Papadima-Sophocleous et al (2012) report the results of an experiment that sought to measure the impact of the iPod Touch upon L2 English oral reading skills. The six-week project involved fifteen intermediate level Cypriot university students who downloaded three texts with accompanying audio recordings that served as models of pronunciation.…”
Section: Discussionmentioning
confidence: 99%
“…Papadima-Sophocleous et al (2012) report the results of an experiment that sought to measure the impact of the iPod Touch upon L2 English oral reading skills. The six-week project involved fifteen intermediate level Cypriot university students who downloaded three texts with accompanying audio recordings that served as models of pronunciation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite what group a participant was in, the most frequent reasoning for preferring the interface he or she used was that it made support strategy use easier. This follows appropriation theory (Papadima‐Sophocleous & Charalambous, )—the participants in each group found their interface to be more familiar and thus more useful.…”
Section: Discussionmentioning
confidence: 70%
“…This study is also guided by appropriation theory (Papadima‐Sophocleous & Charalambous, ), which describes how an innovative artifact, such as an e‐book, is foreign until it is incorporated into one's life. Whether an artifact is incorporated hinges upon its proximity to other familiar items; in the case of an e‐book, this may be its physical properties and how one can manipulate the text with it.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study showed that most of the articles (N = 50) used software to improve the skills mentioned before. However, five of the studies used mobile applications (Corkett & Benevides, 2016;Nordness et al, 2011;Papadima-Sophocleous & Charalambous, 2014;Skiada et al, 2014;.…”
Section: Skills That Need Improvement and Technological Toolsmentioning
confidence: 99%
“…A total of 36 articles resulted in statistically insignificant improvement in reading, writing, and math. First of all 14 of the articles covered skills related to reading (Ciullo et al 2015;Cullen, et al, 2014;Cullen, et al, 2013;Dolan, et al, 2005;Keyes et al, 2016;Klemes et al, 2006;Papadima-Sophocleous & Charalambous, 2014;Regan et al, 2014;Scheeler et al, 2010;Silver-Pacuilla, 2006;Wade et al, 2010;White & Robertson, 2015).…”
Section: Effects Of the Technology Use On Students' Performances Relamentioning
confidence: 99%